2014
DOI: 10.1097/bor.0000000000000119
|View full text |Cite
|
Sign up to set email alerts
|

Myositis registries and biorepositories

Abstract: Purpose of review Clinical registries and biorepositories have proven extremely useful in many studies of diseases, especially rare diseases. Given their rarity and diversity, the idiopathic inflammatory myopathies, or myositis syndromes, have benefited from individual researchers’ collections of cohorts of patients. Major efforts are being made to establish large registries and biorepositories that will allow many additional studies to be performed that were not possible before. Here we describe the registrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 151 publications
(200 reference statements)
0
2
0
Order By: Relevance
“…In the future, emphasis needs to be placed on multidisciplinary collaborative investigations of genetic and environmental risk factors and their interactions, as well as pathogenic mechanisms in homogeneous, well-defined phenotypes, utilizing the many IIM registries and repositories that have been developed to allow for the most cost-effective strategies 186 . More investment in these areas seems appropriate to develop preventative strategies and to allow for innovative approaches to treatment as new pathways to disease are discovered.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, emphasis needs to be placed on multidisciplinary collaborative investigations of genetic and environmental risk factors and their interactions, as well as pathogenic mechanisms in homogeneous, well-defined phenotypes, utilizing the many IIM registries and repositories that have been developed to allow for the most cost-effective strategies 186 . More investment in these areas seems appropriate to develop preventative strategies and to allow for innovative approaches to treatment as new pathways to disease are discovered.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the rarity of JDM cases, it is extremely hard to carry out functional assays to understand what underlies B cell dysfunction in JDM. Nevertheless, large cohorts of JDM patients such as Juvenile Dermatomyositis Cohort Biomarker Study and Repository (UK and Ireland) (JDCBS) and the Myositis Genetics Consortium (MyoGen) are now being used to address how B cell function is altered in children with JDM (85, 86). For example, using patients recruited to the JDCBS, it was recently reported that CD19 + CD24 hi CD38 hi B cells are expanded in the peripheral blood of JDM patients that are naïve of immunosuppressive treatment, demonstrating that similarly to other rheumatic disorders normal B cell development is affected.…”
Section: Juvenile Dermatomyositismentioning
confidence: 99%